Job satisfaction among working mothers in Kuala Lumpur - Loggeta, Panirselvam (2019)
Naturally, mothers will spend their time rising up a family at home. However, today cost of living, especially in city areas such as Kuala Lumpur, mothers have to work to lessen the income burden to the family. Are these working mothers satisfied with their jobs? Therefore the purpose of this research is to examine job satisfaction among working mothers in Kuala Lumpur using work conditions, supervisors, co-workers, pay and promotion as the independent variables. Six hypotheses were developed for this study. Data were collected using online research form. A total of 392 responses was collected from working mothers in Kuala Lumpur using the convenience sampling approach. Using SPSS version 25.0, the data collected were analyzed using descriptive, correlation, and regression analysis. The correlation analysis shows that work conditions, supervisors, co-workers, pay and promotion have significant and positive relationship with job satisfactions among working mothers in Kuala Lumpur. The regression R2 = 0.825 suggest that 82.5 percent of the variance in working mothers’ job satisfaction can be explained by work conditions, supervisors, co-workers, pay and promotion and pay (β = .350) was the best predictor of job satisfaction among working mothers. This is followed by promotion (β = .331), working condition (β = .213) and coworker (β = .112). The findings of this study are similar to other earlier studies where pay is the main reason why working mothers are pursuing their job to raise up a family instead of pursing their intention of spending more time and attention to their family at home. The findings in this research might be able to extend the research to less focused community members like transgender and handicaps respondents to study their job satisfaction.